PENGARUH KOMUNIKASI TERHADAP EFEKTIVITAS KERJA KARYAWAN PADAPT.CHANGSHIN INDONESIA DI KARAWANG - Sri devi sigiro; Fuji isyanto (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to analyze the influence on the effectiveness of employee performance in PT. Changshin, Karawang. Communication has a close relationship with employee performance, this can be explained that the better the communication of employees in conveying to the public or internal and external parties, the better the performance of employees. This research method uses a quantitative approach with questionnaire surveys and in-depth interviews, this study identifies various communication elements that affect employee performance, with a population of 30 respondents. Based on the results of this study, it shows that good effective communication significantly increases the effectiveness of employee performance. quality of information, proper communication media, good interpersonal relationships play an important role in improving performance, however, these barriers in communication are such as culture and language are still a challenge. Indications of the lack of employee work effectiveness can be seen from low productivity, high absenteeism, and low job satisfaction. To increase the effectiveness of employee performance, it is recommended to provide communication training, optimization of communication technology, as well as improvement of interpersonal relationships and conflict management, the implementation of better communication strategies is expected to increase the productivity and performance of all employees at PT. Changshin Indonesia.